ILC2s Control Microfilaremia During Litomosoides sigmodontis Infection in Rag2-/- Mice - Reichwald, Julia J.; Risch, Frederic; Neumann, Anna-Lena; Frohberger, Stefan J.; Scheunemann, Johanna F.; Lenz, Benjamin; Ehrens, Alexandra; Strutz, Wiebke; Schumak, Beatrix; Hoerauf, Achim; Hübner, Marc P. (Frontiers in Immunology, 2022)
Group 2 innate lymphoid cells (ILC2s) are inducers of type 2 immune responses, but their role during filarial infection remains unclear. In the present study, we used the Litomosoides sigmodontis rodent model of filariasis to analyze ILC2s during infection in susceptible BALB/c mice that develop a chronic infection with microfilaremia and semi-susceptible C57BL/6 mice that eliminate the filariae shortly after the molt into adult worms and thus do not develop microfilaremia. ILC2s (CD45+ Lineage- TCRβ- CD90.2+ Sca-1+ IL-33R+ GATA-3+) were analyzed in the pleural cavity, the site of L. sigmodontis infection, after the infective L3 larvae reached the pleural cavity (9 days post infection, dpi), after the molt into adult worms (30dpi) and during the peak of microfilaremia (70dpi). C57BL/6 mice had significantly increased ILC2 numbers compared to BALB/c mice at 30dpi, accompanied by substantially higher IL-5 and IL-13 levels, indicating a stronger type 2 immune response in C57BL/6 mice upon L. sigmodontis infection. At this time point the ILC2 numbers positively correlated with the worm burden in both mouse strains. ILC2s and GATA-3+ CD4+ T cells were the dominant source of IL-5 in L. sigmodontis-infected C57BL/6 mice with ILC2s showing a significantly higher IL-5 expression than CD4+ T cells. To investigate the importance of ILC2s during L. sigmodontis infection, ILC2s were depleted with anti-CD90.2 antibodies in T and B cell-deficient Rag2-/- C57BL/6 mice on 26-28dpi and the outcome of infection was compared to isotype controls. Rag2-/- mice were per se susceptible to L. sigmodontis infection with significantly higher worm burden than C57BL/6 mice and developed microfilaremia. Depletion of ILC2s did not result in an increased worm burden in Rag2-/- mice, but led to significantly higher microfilariae numbers compared to isotype controls. In conclusion, our data demonstrate that ILC2s are essentially involved in the control of microfilaremia in Rag2-/- C57BL/6 mice.